Explaining Employer Support for Welfare State Development in The Netherlands - Oude Nijhuis, Dennie (TSEG - The Low Countries Journal of Social and Economic History, 2019)
In recent years, business-centered explanations of welfare state development have challenged conventional perspectives on the welfare state. This new scholarship argues that employer and other business groups have acted as major proponents of welfare state expansion during crucial moments in history. This article investigates the claims of this new scholarship through an analysis of the attitudes of the main employer associations towards the introduction and expansion of social insurance programs in the Netherlands. The article finds no evidence for the claim that these associations supported the introduction and expansion of social insurance programs because they expected to derive economic benefits from the development of these programs. It shows that instances of active employer support for social insurance expansion generally came about as a strategic response aimed at preventing the coming about of more costly alternatives.